Análise do sistema regional de inovação no estado do Tocantins - Almeida, Ygor Freitas de (Universidade Federal do Tocantins, 2018)
This dissertation deals with the analysis of the innovation environment in the state of Tocantins. For this purpose, the concept of Triple Helix was applied, which in other words means how Government, Universities and Companies can combine to generate innovation. It was used the data collection of innovative programs and projects launched and/or published by the institutions within each Helix. In addition, information on human resources was collected, specifically master's and doctoral programs and its number of masters and doctorates present in the state. The discussion is also supplied by the ranking of Universities published annually by the Folha de São de Paulo, besides the number of patents registered in the state. Finally, in view of the implementation phase of the Tocantins Technological Park, considering it as a development tool capable of bringing together the three agents of innovation [Government, Universities and Companies], it was decided to apply the Strategic Situational Planning - SSP, as a way of verifying, according to the view of the actors of each Helix, what would be the constraints and therefore the necessary actions to give the institutional structure that is being developed in order to make C, T & I viable in the state of Tocantins. The results point to the need to change vision in each one of the Helix, representing an analysis tool for the process of building strategies to act aiming at the transformation of the current scenario, in an environment where innovation is the driving force of the economic development policies of the state of Tocantins.